Transformasi Partisipasi Masyarakat dalam Pemilukada DKI Jakarta 2017 - Dina - Fadiyah (Jurnal Ilmu Politik dan Pemerintahan, 2017)
This paper analyzes the transformation of public participation in the election of regional heads in DKI Jakarta in 2017. In the 2017 Jakarta Regional Head Election, the people participation is very high, one of which is seen from various actions during the election period. The formerly passive society suddenly became participatory. The people of DKI Jakarta, known as apathetic, become very concerned. This research uses descriptive qualitative method with a review of participation theory. The hypothesis of this study that the change of society from passive and apathetic tendency to political contestation become active and participative society because a very crucial factor is the existence of actors who "attract".